2009
DOI: 10.1139/t09-055
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between matric potential and dielectric properties of organic free soils: a sensitivity study

Abstract: High-frequency electromagnetic determination of moisture in porous media, (e.g., soil) is based on the strong relationship between volumetric water content and relative dielectric permittivity. In particular, in fine-grained soils the movement of water is influenced by different surface-bonding forces due to interface processes. The interface effects lead to a number of dielectric relaxation processes (free- and bound-water phase, Maxwell–Wagner effect, counterion relaxation effects). These relaxation processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 81 publications
1
65
0
1
Order By: Relevance
“…The experimental results indicate three active relaxation processes in the investigated frequency-temperaturepressure range: two weak high-frequency processes α and β (associated with different binding states of water in the porous material) and a strong low-frequency process γ associated with counter-ion relaxation, Maxwell-Wagner effects and ice. To characterize the dielectric relaxation behaviour, a generalized fractional dielectric relaxation model (Wagner et al, 2007(Wagner et al, , 2011 was applied assuming three active relaxation processes with relaxation time of the ith process modelled with an Eyring equation (Wagner and Scheuermann, 2009). The strong γ process exhibits an apparent activation energy of 51 kJ mol −1 and shows a clear deviation from simple Debye behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental results indicate three active relaxation processes in the investigated frequency-temperaturepressure range: two weak high-frequency processes α and β (associated with different binding states of water in the porous material) and a strong low-frequency process γ associated with counter-ion relaxation, Maxwell-Wagner effects and ice. To characterize the dielectric relaxation behaviour, a generalized fractional dielectric relaxation model (Wagner et al, 2007(Wagner et al, , 2011 was applied assuming three active relaxation processes with relaxation time of the ith process modelled with an Eyring equation (Wagner and Scheuermann, 2009). The strong γ process exhibits an apparent activation energy of 51 kJ mol −1 and shows a clear deviation from simple Debye behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…where free enthalpy of activation or Gibbs energy G i (T , p) [kJ mol −1 ] and entropy of activation of the ith (Wagner et al, 2007;Wagner and Scheuermann, 2009).…”
Section: Dielectric Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, soils generally respond dielectrically in a broad frequency range. These responses not only originate from pore water but also from the soil composition, structure, and mineralogy, as well as many other important soil characteristics [18,19]. With continuing research, the dielectric soil property at around 1 GHz is found to be not only a function of water content, but also of porosity and saturation [20,21,22].…”
Section: Introductionmentioning
confidence: 99%